Diagnosa Hipertensi Dengan Menggunakan Metode Certainty Factor - Ahmad Kurniawan Prahadi; Yani Maulita; Magdalena Simanjuntak (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Hypertension does not occur suddenly, but through a process that lasts quite a long time. Hypertension is an increase in blood pressure in the arteries that is systemic in nature or lasts continuously for a long period of time. Uncontrolled high blood pressure for a certain period will cause permanent high pressure called hypertension. Studies conducted by health institutions in the UK stated that in general hypertension is experienced by men and women aged 48.5 years. Although there are young people who suffer from hypertension, the percentage is relatively small. With this fact, hypertension is included in the group not a congenital disease. In diagnosing hypertension, of course, it can not only be done by measuring blood pressure, but requires further examination by a doctor. However, to see a doctor the patient must queue with another patient to be examined. This will certainly make the patient bored and will even cause blood pressure to increase even more due to waiting too long to be treated. To deal with the problems mentioned above, it is necessary to build an expert system that can diagnose hypertension quickly and get a treatment solution like a doctor using the Certainty Factor method. The certainty factor is a derivation and development of the conditioned probability theory (Bayes theorem). The certainty factor is obtained from the operation of reducing the value of belief (measure of belief) by the value of distrust (measure of disbelief). The main purpose of using the certainty factor is to process the uncertainty of facts and phenomena by avoiding the need for large data and calculations.